Evaluation of the intensity of lateral and vertical wear of rails under passing trains - A. Ya. Kogan (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
The article presents the fundamentals of methods for estimating lateral and vertical wear of the rail head, as well as their intensity, depending on the geometric and force interaction of the rails and wheels of the rolling stock running in a given section in a stochastic setting. The problem is solved for the general case of the entire manifold of the rolling stock (including various design features) running along a curve of a given radius for a given elevation of the outer rail (or tangent section). The track section is characterized by the main dynamic parameters of the structure of railway superstructure, as well as the specified probabilistic characteristics of random processes that determine its state in terms of plan, profile and level. The quantitative estimates of lateral and vertical wear of the rail head in the article can be used to solve a number of operational problems. For example, it is possible to estimate the effect of the mismatch between the elevation of the outer rail in the curves on the lateral wear of the outer rail and the vertical wear of the inner rail with the mixed traffic of freight and passenger trains.